Multiple Chromoanasynthesis in a Rare Case of Sporadic Renal Leiomyosarcoma: A Case Report - Anoshkin, Kirill Igorevich; Karandasheva, Kristina Olegovna; Goryacheva, Kristina Mikhaylovna; Pyankov, Denis Valer’yevich; Koshkin, Philipp Aleksandrovich; Pavlova, Tatiana Vladimirovna; Bobin, Alexandr Nikolaevich; Shpot, Evgeniy Valer’yevich; Chernov, Yaroslav Nikolayevich; Vinarov, Andrei Zinov’yevich; Zaletaev, Dmitry Vladimirovich; Kutsev, Sergei Ivanovich; et al. (Frontiers in Oncology, 2020)
We present the genetic profile of kidney giant leiomyosarcoma characterized by sequencing of 409 cancer related genes and chromosomal microarray analysis. Renal leiomyosarcomas are extremely rare neoplasms with aggressive behavior and poor survival prognosis. Most frequent somatic events in leiomyosarcomas are mutations in the TP53, RB1, ATRX and PTEN genes, chromosomal instability and chromoanagenesis. 67-year-old woman presented with a right kidney completely replaced by tumor. Immunohistochemical reaction on surgical material was positive to desmin and smooth muscle actin. Molecular genetic analysis revealed that tumor harbored monosomy of chromosomes 3 and 11, gain of Xp (ATRX) arm and three chromoanasynthesis regions (6q21-q27, 7p22.3-p12.1 and 12q13.11-q21.2), with MDM2 and CDK4 oncogenes copy number gains, whereas no CNVs or tumor specific SNVs in TP53, RB1 and PTEN genes were present. We hypothesize that chromoanasynthesis in 12q13.11-q21.2 could be a trigger of observed chromosomal instability in this tumor.